Vietnam : 2010 Article IV Consultation; Staff Report and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2010)
Real GDP growth slowed somewhat to 5.3 percent in 2009, its slowest pace since 2000, though Vietnam was among the better performers in developing Asia. An immediate challenge is to consolidate the current stable macroeconomic conditions through prudent policies and better communications. Over the medium term, Vietnam needs to implement fiscal consolidation with a view to lowering the public debt-to-GDP ratio. IMF staff welcomed the move to modernize and strengthen fiscal management. Staff argued for further reforms, as state-owned commercial banks (SOCBs) still do not totally follow market-based business principles.